Estilos de crianza parental y las conductas disruptivas en los niños. - Armijos Piedra, Tania Rosalía; Castro Ponce, Mónica Cecibel (Machala : Universidad Técnica de Machala, 2018)
The work presented tries to determine the influence of parental parenting styles on the appearance and maintenance of disruptive behaviors in children, under the epistemological support of the systemic approach, considering that this model, because it is holistic, deals with the behavior of an individual and their environment, especially the family, as determinants related to each other; In fact, the process of socialization in the family is the first and main means that provides and provides feedback at the behavioral and emotional level of an adequate and expected child adaptation, by linking the practice of: attitudes, delimitation of norms-limits, values, fulfillments of role-functions and expressions of communication-affection. The categories of analysis contemplated in the work were: parenting styles, family functionality and disruptive behaviors. Six parents participated in the study, their children between the ages of 5 and 9 years and the teachers respectively; these families reside in the urban parish El Cambio and other nearby sites belonging to the Machala canton. It corresponds to a mixed type research (qualitative-quantitative), of narrative-biographical design for the discursive contribution that the representatives of the children expressed and of descriptive-interpretative scope seeking to characterize and explain the family dynamics and the behaviors that result from the parental educational practices.
El trabajo que se presenta intenta determinar la influencia de los estilos de crianza parental en la aparición y mantenimiento de conductas disruptivas en niños, bajo el respaldo epistemológico del enfoque sistémico, considerando que este modelo por ser holístico trata a la conducta de un individuo y su entorno, especialmente el familiar, como factores determinantes relacionados entre sí; de hecho, el proceso de socialización en la familia es el primer y principal medio que provee y retroalimenta a nivel comportamental y emocional una adaptación infantil adecuada y esperada, al vincular la práctica de: actitudes, delimitación de normas-límites, valores, cumplimientos de funciones-roles y expresiones de comunicación-afecto. Las categorías de análisis contempladas en el trabajo fueron: estilos de crianza parental, funcionalidad familiar y conductas disruptivas. Participaron en el estudio seis padres de familia, sus hijos de edades comprendidas entre 5 y 9 años y los docentes respectivamente; estas familias residen en la parroquia urbana El Cambio y otros sitios aledaños perteneciente al cantón Machala. Corresponde a una investigación de tipo mixto (cualitativo-cuantitativo), de diseño narrativo-biográfico por el aporte discursivo que manifestaron los representantes de los niños y de alcance descriptivo-interpretativo buscando caracterizar y explicar la dinámica familiar y los comportamientos que resultan producto de las prácticas educativas parentales.
Keywords: FAMILIA; CRIANZA FAMILIAR; CONDUCTA DISRUPTIVA; CONTEXTO